Organisational career conversations: exploring the experiences and perceptions of professional services line-managers in higher education - Sarah Allbeson (Journal of Learning Development in Higher Education)
Many organisations are not confident about their career development strategy, but career conversations with line-managers are one of the main ways in which it is carried out (Hirsh, 2021). The public sector is distinctive in its approach towards staff and the careers of university professional services staff is an under-researched area including the shape of career trajectories for third space professionals and how these are managed by institutions (Whitchurch, 2022). This study examines the experiences and perceptions of line-managers in professional services in UK Higher Education Institutions (HEIs) in holding career conversations. A qualitative approach using semi-structured interviews and inductive thematic analysis identified three themes focusing on the ways in which line-managers (i) encourage and enable career conversations taking place, (ii) balance the dynamics of career conversations between individual and organisational needs, and (iii) express opinions which challenge the status quo of training and development and career progression in UK HEIs. The discussion identifies that line-managers value career conversations and feel equipped to hold them but consider they need more support in terms of the organisational infrastructure that lies behind a career conversation. There was evidence of a hybrid career concept in which there are elements of reciprocal responsibility for career management between the organisation and the individual. The study therefore finds that organisational support needs re-evaluation and barriers to career progression for professional services staff are a priority for the sector to address, highlighting that doing so can promote social justice and recognise the impact of social context in contemporary organisational career development practice.